Neutrophil and Nanoparticles Delivery to Tumor: Is It Going to Carry That Weight? - Vishnevskiy, Daniil A.; Garanina, Anastasiia S.; Chernysheva, Anastasia A.; Chekhonin, Vladimir P.; Naumenko, Victor A. (Advanced healthcare materials, 2021)
The application of cell carriers for transporting nanodrugs to the tumor draws much attention as the alternative to the passive drug delivery. In this concept, the neutrophil (NΦ) is of special interest as this cell is able to uptake nanoparticles (NPs) and cross the vascular barrier in response to tumor signaling. There is a growing body of literature describing NP–NΦ interactions in vitro and in vivo that demonstrates the opportunity of using these cells to improve the efficacy of cancer therapy. However, a number of conceptual and technical issues need to be resolved for translating the technology into clinics. The current review summarizes the recent advances and challenges associated with NP–NΦ interactions, with the special focus on the complex interplay between the NP internalization pathways and the modulation of NΦ activity, and its potential consequences for nanodrug delivery. The review covers several important aspects of neutrophil‐nanoparticles interactions including internalization mechanisms, delivery routes to tumor bed, and potential nanomedicines impact on cellular function. The tight crosstalk between the mechanisms responsible for nanoparticles uptake and neutrophil regulation pathways should be taken into consideration while designing neutrophil‐based drug delivery systems.